A new species of crayfish of the genus Cherax from Indonesian New Guinea (Crustacea, Decapoda, Parastacidae) - Christian Lukhaup; Rury Eprilurahman (Zoosystematics and Evolution, 2022)
A new species of the genus Cherax is described and illustrated. Cherax wagenknechtae sp. nov., endemic to the Beraur and Klasabun River drainages in the western part of the Kepala Burung (Vogelkop) peninsula, West Papua, Indonesia, is described, figured and compared with its closest relatives, Cherax pulcher Lukhaup, 2015. The new species may be easily distinguished from Cherax pulcher by the shape of the chelae, rostrum and body, and coloration.